PROFESSIONAL AND PEDAGOGICAL COMPETENCE AS A COMPONENT OF PROFESSIONAL TRAINING FUTURE ECONOMICS MANAGERS (Pedagogy of Higher and Secondary Education, 2007)
The different definitions of “competency” and “competence” are analyzed in this article. An integral model of a prospective manager in economics is defined to be effective in combined competency integration which is necessary to fulfill a specific task and to provide labour resources’ mobility in this sphere.